Correction: Target-induced duplex–triplex transition for ratiometric detection of adenosine triphosphate. Issue 41 (17th October 2017) - Yao, Shujuan; Gao, Yanhua; Wang, Wen; Ni, Donghua; Zhang, Kaixian; Li, Ling; Du, Jianqiang; Cui, Xiujuan
Abstract : Correction for 'Target-induced duplex–triplex transition for ratiometric detection of adenosine triphosphate' by Shujuan Yao et al., Anal. Methods, 2017, 9, 3244–3248.